2020
DOI: 10.1136/injuryprev-2020-043829
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art review: preventing child and youth pedestrian motor vehicle collisions: critical issues and future directions

Abstract: AimTo undertake a comprehensive review of the best available evidence related to risk factors for child pedestrian motor vehicle collision (PMVC), as well as identification of established and emerging prevention strategies.MethodsArticles on risk factors were identified through a search of English language publications listed in Medline, Embase, Transport, SafetyLit, Web of Science, CINHAL, Scopus and PsycINFO within the last 30 years (~1989 onwards).ResultsThis state-of-the-art review uses the road safety Saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 68 publications
0
27
0
1
Order By: Relevance
“…Victims involved in MVCs as a passenger or as a pedestrian represented 80% or more of all mechanisms of MVC. A recent systematic review found that child pedestrian safety is affected by three main factors (i.e., built environment, drivers, and vehicles) and four cross-cutting critical issues (i.e., reliable collision and exposure data, evaluation of interventions, evidence-based policy, and intersectoral collaboration) [16]. To this end, the WHO recommends the Safe System Approach, which considers people's vulnerability to serious injuries through a system designed to be more accepting of human error [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Victims involved in MVCs as a passenger or as a pedestrian represented 80% or more of all mechanisms of MVC. A recent systematic review found that child pedestrian safety is affected by three main factors (i.e., built environment, drivers, and vehicles) and four cross-cutting critical issues (i.e., reliable collision and exposure data, evaluation of interventions, evidence-based policy, and intersectoral collaboration) [16]. To this end, the WHO recommends the Safe System Approach, which considers people's vulnerability to serious injuries through a system designed to be more accepting of human error [17].…”
Section: Discussionmentioning
confidence: 99%
“…A specific preventative intervention in pediatric MVC-related injuries is the implementation of CRSs. Studies have demonstrated that the correct use of CRSs reduces mortality and injury frequency and severity in infants and children and consequently reduces injuryrelated sequelae and disability in this vulnerable group [7][8][9]16,20]. While Costa Rica has implemented legislation mandating the use of CRSs [21], Panama and Guatemala, lack specific legislation for CRS in compliance with international standards.…”
Section: Discussionmentioning
confidence: 99%
“…6 7 However, there is little empirical information on the relationship between built environment and PCMVC across North American cities, and little agreement on the influence of pedestrian and cyclist volumes on this relationship. 3 Previous research in Toronto, Canada found that the proportion of children walking to school was not associated with more child PCMVC, if the built environment around schools was safer. 8 The purpose of this study was to assess the built and social environment correlates of child PCMVC in diverse Canadian urban/suburban environments, so as to help identify features of safe roadway environments.…”
Section: Introductionmentioning
confidence: 97%
“…As well, traffic levels, pedestrian density, road density, crossing major roads, and mixed land use were all associated with increased rates of injury incidence. More recently, Cloutier et al [ 20 ] completed a review from the perspective of a Safe System approach. They highlighted three key influences: the built environment, vehicles, and drivers.…”
Section: Introductionmentioning
confidence: 99%